Cuban Ocular Toxoplasmosis Epidemiology Study (COTES): Clinical Features in 279 Patients from Central Cuba - J Daniel Diaz; Jorge L Bustillo; Idarmes C Pacheco; David C Gritz (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2016)
Purpose: To characterize the clinical features of ocular toxoplasmosis (OT) in Central Cuba. Methods: A database at a large regional referral center was searched for patients who, from April 1, 2011 to May 31, 2013, had the potential diagnosis of OT. Inclusion criteria were the clinical diagnosis of OT, characterized by focal retinochoroidal inflammation. Medical records were reviewed to confirm inclusion criteria (visual acuity recorded in decimal form). Results: 279 patients (329 total eyes) were affected with OT. Overall, 66.7% were diagnosed with acquired OT with a mean age of 35.4 years and 1.8% with congenital OT with a mean age of 3.4 years. The time of onset of OT could not be determined in 28.3% (n=79) of patients. Patient clinical presentations were posterior uveitis (72.8 %), quiescent retinochoroiditis (16.1 %), and panuveitis (11.1%). Fourteen percent of patients had a slight decrease (0.9-0.6) in visual acuity, 44.4% a moderate decrease (0.5-0.2), and 41.6% a marked decrease (< 0.1). Conclusion: There exist large numbers of patients with active toxoplasmic uveitis in the Central Cuban region. To our knowledge, this is the first report in the English medical literature describing OT in the Cuban population.